Narratives in Cypriot Greek mono- and bilingual children with SLI - Theodorou, Eleni; Grohmann, Kleanthes K. (My University, 2010)
Narrative ability is one of the most promising ways to assess communicative competence in children: Coordination of lexical, morphosyntactic, phonological, and pragmatic elements is needed to produce narrations. Narratives might even serve as a diagnostic tool for Specific Language Impairment, since children with Specific Language Impairment are reported to have difficulties producing (oral) narratives. Different approaches are available for narrative analysis. In the present study, the Renfrew Bus Story Test was used to investigate narrative ability in mono- and bilingual children aged between 5 and 10 years with typical and impaired language development acquiring Cypriot Greek. The findings suggest that narratives can indeed be a useful tool to identify and assess language-impaired children.
Keywords: Cypriot Greek; Mono- and bilingual first language acquisition; Narrative ability; Renfrew bus story test; Specific language impairment